Features of the "Monumental" Policy of the United States in Relation to the Conflicts of the Cold War (on the Example of Monuments in Washington, D.C.) - Влада Евгеньевна Дергачева; Юрий Георгиевич Чернышов (Известия Алтайского государственного университета, 2023)
In this article, the authors analyze the unique features of the United States' "monumental" policy in relation to the conflicts of the Cold War and the associated memorial and commemorative spaces within the metropolitan region. Specifically, the authors focus on the two Cold War conflicts that are commemorated on the National Mall in Washington, D.C. — the Korean War (1950-1953) and the Vietnam War (19641975). The Vietnam Veterans Memorial (1982) and the Korean War Veterans Memorial (1995) are among the monumental objects that commemorate these conflicts, along with the Three Soldiers Monument (1984) and the Vietnam Women's Memorial (1993), which were later added to the Vietnam Veterans Memorial. To examine the evolution and specific characteristics of the American "monumental" policy regarding the history of the Cold War, the authors employed various sources, including artifacts of "monumental" policy such as monuments, memorial complexes, and architectural structures; official documents on monumental projects; official websites of memorials and their funds; materials on planning, construction, and preservation of memorials; memoirs and interviews of architects; articles in the media; opinion polls; reviews from visitors to monumental objects. By tracing the history of the creation of these monumental objects, the authors aim to evaluate the degree of influence of civil society on official memory politics and to understand how assessments of Cold War conflicts have evolved in the United States.